2008
DOI: 10.1211/jpp.60.6.0017
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial influence of capsaicin on lipid peroxidation, membrane-bound enzymes and glycoprotein profile during experimental lung carcinogenesis

Abstract: This study was designed to examine the impact of a principal component of hot red peppers and chilli peppers, capsaicin, on alterations in lipid peroxidation, membrane-bound enzyme profiles and glycoprotein levels during benzo(a)pyrene (BP)-induced lung cancer in Swiss albino mice. BP (50 mgkg(-1)) induced deleterious changes that were that revealed by alterations in lipid peroxidation, membrane-bound enzyme (Na+/K+ ATPase, Ca2+ ATPase and Mg2+ ATPase) activity, levels of total protein and protein-bound carboh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…At the termination of the study (38 weeks), capsaicin feeding during either the initiation or promotion phase reduced the frequency of tongue squamous cell papillomas and squamous cell carcinomas (NQO alone, 9/15 rats with tongue tumors; NQO plus 10 weeks capsaicin, 5/17 rats with tongue tumors [not significant]; NQO plus 28 weeks of capsaicin, 3/14 rats with tongue tumors [p<0.05]). In a series of closely related experiments using Swiss albino mice, capsaicin was shown to exert its chemoprotective effects via several different mechanisms against benzo(a)pyrene (BP)-induced lung cancer (Anandakumar et al 2008;Anandakumar et al 2008aAnandakumar et al , 2008bAnandakumar et al2009aAnandakumar et al , 2009b; Anandakumar, P., Kamaraj, S., Jagan, S., Ramakrishnan, G., Naveenkumar, et al 2009). Due to the closely related nature of methods and somewhat overlapping results, key results from all 8 publications are grouped into one entry in Table 4.…”
Section: Teel and Huynh 1999mentioning
confidence: 99%
“…At the termination of the study (38 weeks), capsaicin feeding during either the initiation or promotion phase reduced the frequency of tongue squamous cell papillomas and squamous cell carcinomas (NQO alone, 9/15 rats with tongue tumors; NQO plus 10 weeks capsaicin, 5/17 rats with tongue tumors [not significant]; NQO plus 28 weeks of capsaicin, 3/14 rats with tongue tumors [p<0.05]). In a series of closely related experiments using Swiss albino mice, capsaicin was shown to exert its chemoprotective effects via several different mechanisms against benzo(a)pyrene (BP)-induced lung cancer (Anandakumar et al 2008;Anandakumar et al 2008aAnandakumar et al , 2008bAnandakumar et al2009aAnandakumar et al , 2009b; Anandakumar, P., Kamaraj, S., Jagan, S., Ramakrishnan, G., Naveenkumar, et al 2009). Due to the closely related nature of methods and somewhat overlapping results, key results from all 8 publications are grouped into one entry in Table 4.…”
Section: Teel and Huynh 1999mentioning
confidence: 99%
“…We have recently reported the chemopreventive action of CAP in modulating pulmonary antioxidant defense system and stabilizing mitochondrial enzyme system in lung cancer [7,10]. Our studies have also proved the influence of CAP on modulating lipid peroxidation, membrane‐bound enzymes and glycoprotein profile during lung carcinogenesis [11].…”
Section: Introductionmentioning
confidence: 79%
“…Our results are in agreement with these findings as we have observed increased activities of lysosomal proteases cathepsin‐D, cathepsin‐B, together with β‐ d ‐glucosidase, β‐ d ‐galactosidase, β‐ d ‐glucuronidase, β‐ d ‐ N ‐acetylglucosaminidase and acid phosphatase in the lung and serum of animals having cancer. CAP has been reported to possess antioxidant/free radical‐quenching property and inhibit free radical‐mediated oxidative stress [11]. CAP, by its antiperoxidative effect, traps peroxyl radical and acts by scavenging free radicals and quenching lipid peroxidative chains [41].…”
Section: Discussionmentioning
confidence: 99%
“…(De and Ghosh, 1993). Studies from our laboratory have also revealed the chemopreventive action of CAP in different dimensions (Anandakumar et al, 2008a); (Anandakumar et al, 2008b); (Anandakumar et al, 2008c).…”
Section: Introductionmentioning
confidence: 84%